Het didactiseren van bewuste taalvaardigheid: grammaticale concepten ingebed in hun grammaticale en taalcontrastieve context - Leenders, G.p.m.; van Amstel, M.O.; de Graaff, R.; van Koppen, M. (Dutch Journal of Applied Linguistics, 2024)
Various contextualized and cross-linguistic approaches of grammar teaching have yielded significant transfer effects on both metalinguistic knowledge and proficiency in reading, writing, listening, and speaking in the first and second languages. Nevertheless, a similar approach is absent in language teaching in the Netherlands, perpetuating the discrepancy between the intended, implemented, and attained objectives. This study endeavors to remedy this discrepancy by examining the effective characteristics of teaching materials promoting language awareness. To this end, a contextualized, cross-linguistic lesson series on the concept of ‘syntactical function’ was designed, targeting upper secondary students (aged 15-16) drawing from four design principles and an analysis of the Dutch, the English and the German language. Subsequently, the lesson series underwent expert consultation, focus group interviews and various impact measurements, yielding a significant positive influence on students’ motivation and language awareness in all three languages. This underlines the potential value of teaching materials promoting language awareness.